Using an Adaptive Learning Environment for Conceptual and Procedural Knowledge Development - Pramudya Ananta, Gede (2011)
Researchers report that learners find the flexibility of hypermedia learning systems both a strength and a weakness. On the one hand, the systems allow learners to work at their own pace and allow a great deal of control of the learning paths they take. For some learners this is a blessing, bur others feel overwhelmed by the large number of available option and suffer from information overload. One approach to this is to provide learners with an adaptive learning system that initially limits the choices they can make until they mastered they key concepts. During the study, ART-WEB was used to develop a prototype of an adaptive web-based learning environment. The purpose of the prototype was to provide students with a conceptual and procedural knowledge introduction to the multimedia authoring tool HyperStudio. This prototype was trialed with 2 undergraduate and 1 graduate classes. Data were collected by means of questionnaires, interviews, and tracking files of learner use. Coded data were entered into a spreadsheet and then analyzed. The findings showed that the use of adaptive annotation technology supported student learning of basic conceptual and procedural knowledge about the use of the authoring tool. The data suggest that the system provided learners with a well-structured navigation system that made use of textual and visual cues to locate them in hyperspace and to provide feedback on their progress. This supports the findings of other researchers who used the tools in other contexts. This study contributes to the research literatures by showing that web-based learning environments may have a role to play in supporting the development of learner conceptual and procedural knowledge when they are involved in learning a complex skill such as then use of multimedia authoring tool. The tool developed was a prototype and as such would need additional development before being put to general use. However, it did demonstrate a concept and show that such tools may be useful supports in complex, hypermedia learning system.